2007
DOI: 10.1111/j.1365-2915.2007.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium marking of Anopheles mosquitoes detectable by field‐capable X‐ray spectrometry

Abstract: We present a mosquito marking technique suitable for mark-release-recapture that can be used with a hand-held, portable X-ray fluorescence (XRF) spectrometer, which is practical for field measurements. Third instar Anopheles gambiae Giles sensu stricto (Diptera: Culicidae) and Anopheles stephensi Liston larvae were cultured to pupation in water containing rubidium (Rb) Cl at concentrations up to 1000 p.p.m. Rb. Anopheles gambiae larvae survived to adulthood at concentrations as high as 1000 p.p.m. Rb but suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A variety of methods have been used to mark mosquitoes, including dusts [4-9], dyes [10,11], paints [12,13], trace elements [14] and radioactive isotopes [15,16] (see reviews in [1-3]). One of the most common methods of marking mosquitoes externally is to apply micronized particles of dust (also known as powder or pigments), particularly fluorescent dust, to a large number of mosquitoes [1].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods have been used to mark mosquitoes, including dusts [4-9], dyes [10,11], paints [12,13], trace elements [14] and radioactive isotopes [15,16] (see reviews in [1-3]). One of the most common methods of marking mosquitoes externally is to apply micronized particles of dust (also known as powder or pigments), particularly fluorescent dust, to a large number of mosquitoes [1].…”
Section: Introductionmentioning
confidence: 99%
“…Methods to mark mosquitoes have included dyes (Welch et al 2006), paints (Trpis and Hausermann 1986), dusts (Reisen et al 1992, Russell et al 2005), trace elements (Wilkins et al 2007), and radioactive isotopes (Lindquist et al 1967). Hagler and Jackson (2001) reviewed marking techniques for insects and stated that the ideal marker should persist without inhibiting normal biology, should be environmentally safe, cost-effective, and easy to use.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the use of Rb to mark bloodfeeding mosquitoes and to study postbloodmeal behavior for certain species (Kimsey and Kimsey 1984, Liew and Curtis 2004, Wilkins et al 2007). Marking of bloodfed phlebotomine sand ßies has been achieved in the Þeld through detection of radioactive carbon in sand ßies that had been acquired through bloodfeeding on parenterally treated gerbils (Dergacheva et al 1996).…”
Section: Discussionmentioning
confidence: 99%